Enhancement of the direct power control by using backstepping approach for a doubly fed induction generator. Issue 5 (October 2022) - Yessef, Mourad; Bossoufi, Badre; Taoussi, Mohammed; Lagrioui, Ahmed
In this paper, an improved direct power command strategy based on backstepping was designed to ensure the proper operation of DFIG during the electrical grid faults and to control the stator powers through the injection of the reactive power into the electrical grid to guarantee the voltage return. This strategy contributes to the elimination of high peak currents and stabilizes the active power at its desired optimal value. The backstepping controller used to develop this command is based on the lyapunov function in order to guarantee the stability and robustness of the aero-generator. A Matlab/Simulink simulation and a comparative study were carried out to prove the robustness and efficiency of our developed command. Moreover, despite the variable wind speed, the obtained results prove the validation of the developed command with a total harmonic distortion (THD) that does not exceed 0.33%.